Advanced technologies in wastewater treatment : oily wastewaters - Basile, Angelo (Elsevier, 2023)
Advanced Technologies in Wastewater Treatment: Oily Wastewaters focuses on characteristics and innovative treatment technologies of oily wastewater from various resources. Primary and physical treatment methods such as absorption, adsorption, followed by common techniques like coagulation and fluctuation are discussed in detail. Applications of other advanced methods for the treatment of oily wastewaters like utilization of membranes and stripping gases are covered as well. Finally, novel technologies applied in purification of oily wastewaters such as photocatalytic degradation and biological processes are reviewed and future outlooks and prospects are also illustrated.